THE ANALYSIS OF DESTINATION IMAGE ONREVISIT INTENTION WITH TOURISTEXPERIENCE AS A MEDIATING (Survey on Visitors to Goalpara Tea Park Sukabumi) - Yunita Dwi Adzani Mahrifa; Asep Muhamad Ramdan; Dicky Jhoansyah (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
This study aims to examine the influence of destination image on revisit intention, with the impression of tourist experience as a mediating variable, using Goalpara Tea Park in Sukabumi as the case study. As a newly established tourist destination, Goalpara Tea Park has attracted attention for its natural beauty and modern facilities. However, fluctuations in visitor numbers suggest that not all tourists are interested in returning. This study employs a quantitative approach with a total sample of 135 respondents who had previously visited the site. Data was collected through structured questionnaires and analyzed using the Partial Least Squares Structural Equation Modeling (SEM-PLS) method. The results show that destination image has a significant positive effect on both revisit intention and the impression of tourist experience. Furthermore, the impression of tourist experience significantly mediates the relationship between destination image and revisit intention. This indicates that a strong and positive destination image can enhance the quality of tourist experiences, which in turn increases the likelihood of tourists returning in the future. The findings emphasize the importance of aligning promotional content with actual on-site experiences to avoid visitor disappointment. The study provides both theoretical contributions to consumer behavior and marketing literature and practical recommendations for tourism managers inimproving service quality and strategic image-building efforts. Enhancing both the physical and emotional aspects of the tourist journey is vital in fostering lasting impressions and loyalty among visitors